Compensation for Lost Services in a Dependency Claim - Balan, P (Journal of Malaysian and Comparative Law, 2019)
Where a dependent of a deceased person brings an action under section 7(1) of the Civil Law Act 1956 he may claim, not only for the pecuniary or money benefit lost as a result of the deceased’s death, but also the money value of the services, if any which were rendered by the deceased to the dependant during the deceased’s life-time. Speaking of the dependant’s damages Lord Wright explained in the House of Lords in Davies v Powell Duffryn Associated Colleries Ltd, "the damages are to be based on the reasonable expectation of pecuniary benefit or benefit reducible to money value..."